"Visual explanations: images and quantities, evidence and narrative" - "Tufte, Edward R." (Connecticut, 2012)
Describes design strategies - the proper arrangement in space and time of images, words, and numbers - for presenting information about motion, process, mechanism, cause, and effect. Examines the logic of depicting quantitative evidence.
Keywords: Visual communication